Impact of ultraviolet-B radiation on two species of forest dwarf shrubs: bilberry (Vaccinium myrtillus L.) and cowberry (Vaccinium vitis-idaea L.) - Robakowski, Piotr (Polish Academy of Sciences. Institute of Ecology. Publishing Office, 1999)
Impact of UV-B irradiation on chlorophyll content and chlorophyll fluorescence of two dwarf shrub species: Vaccinium myrtillus L. and Vaccinium vitis-idaea L. was investigated. The plants originating from different latitudes were used. The experiment was carried out in the greenhouse. Three variants of ultraviolet-B irradiation were applied: control = 0, lower dose = 11.32 and higher dose = 22.64 kJ m-2 day-1 UV-BBE (biologically effective dose of UV-B). Measurements of chlorophyll fluorescence and chlorophyll content were carried out. The response of dwarf shrubs to the increased UV-B radiation depended on UV-B dose, species traits and provenance. Vaccinium vitis-idaea was less sensitive to UV-B than Vaccinium myrtillus. The permanent discoloration was observed only on Vaccinium myrtillus leaves. The leaf bud break of this species was accelerated at high UV-B dose compared to the control. The UV-B radiation influenced its photosynthetic apparatus: the chlorophyll content in leaves was reduced, the maximal and the steady state fluorescence of chlorophyll were diminished. The chlorophyll content in leaves of Vaccinium vitis-idaea did not change significantly but the relative vitality index and the steady state fluorescence were modified under the influence of the radiation.
Pages 3-13 : illustrations ; 27 cm
Bibliographical references (page 13)
Keywords: UV-B radiation; dwarf shrubs; chlorophyll fluorescence; chlorophyll content; phenology